Workload a-WEAR-ness: Monitoring workload in team sports with wearable technology. A scoping review - Benson, L. C.; Räisänen, A. M.; Volkova, V. G.; Pasanen, K.; Emery, C. A. (Journal of Orthopaedic & Sports Physical Therapy, 2020)
Objectives: To (1) identify the wearable devices and associated metrics used to monitor workload and assess injury risk, (2) describe the situations in which workload was monitored using wearable technology (including sports, purpose of the analysis, location and duration of monitoring, and athlete characteristics), and (3) evaluate the quality of evidence that workload monitoring can inform injury prevention.